2017
DOI: 10.2147/ott.s145763
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion and overall staging of endometrial carcinoma: assessment using fusion of T2-weighted magnetic resonance imaging and diffusion-weighted magnetic resonance imaging

Abstract: BackgroundThe age of onset of endometrial carcinoma has been decreasing in recent years. In endometrial carcinoma, it is important to accurately assess invasion depth and preoperative staging. Fusion of T2-weighted magnetic resonance imaging (T2WI) and diffusion-weighted magnetic resonance imaging (DWI) may contribute to the improvement of anatomical localization of lesions.Materials and methodsIn our study, a total of 58 endometrial carcinoma cases were included. Based on the revised 2009 International Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
2
19
1
Order By: Relevance
“…Although the exact mechanisms remain under discussion, it may be theorized that this reflects the increased cell densities in a larger and presumably faster-growing tumor (31). It is interesting to note that this finding contrasts with that in some previous studies conducted with 1.5-T MRI (13), but confirms in part the results other authors who also used a 3.0-T MRI system for DWI reported previously (20,32), which is consistent Fig. 4.…”
Section: Discussionsupporting
confidence: 86%
“…Although the exact mechanisms remain under discussion, it may be theorized that this reflects the increased cell densities in a larger and presumably faster-growing tumor (31). It is interesting to note that this finding contrasts with that in some previous studies conducted with 1.5-T MRI (13), but confirms in part the results other authors who also used a 3.0-T MRI system for DWI reported previously (20,32), which is consistent Fig. 4.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study found a higher performance using fusion of T2-weighted magnetic with diffusion-weighted MR images, with a sensitivity of 92.3% and specificity of 95.5% for deep myometrial invasion detection. 21 In relation to ultrasound, we obtained a poor result in order to detect the deep myometrial invasion. A recent study analyzing 210 women with proven EC found that both subjective assessment and objective ratios were significant predictors of the myometrial invasion, but subjective assessment was confirmed as the most reliable method to assess myometrial invasion (sensitivity 79% and specificity 73%).…”
Section: Discussionmentioning
confidence: 96%
“…Diagnostic possibilities would be increased after fused T2WI and DWI for lung cancers and BPNMs. T2WI combined with DWI may be a valuable tool for detecting prostate cancer in the overall evaluation of prostate cancer [ 33 , 34 ], and myometrial invasion and staging of endometrial carcinoma [ 35 , 36 ]. Adding DWI to T2WI is helpful for detecting viable tumors after neoadjuvant chemoradiation therapy compared with T2WI alone or PET/CT in patients with locally advanced rectal cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%